Mesenchymal Stem Cells and Clinical Application in Chronic Lung Diseases - Isti Mardiana Soetartio; Triya Damayanti (Faculty of Medicine Universitas Airlangga, 2021)
Mesenchymal stem cells are a multipotent mature non hematopoietic stem cells, with characteristics such as ability to self-renew and differentiate in mesodermal, ectodermal, and endodermal pathway. Mesenchymal stem cells also secrete cytokine and immunoreceptor which regulate micro environment in host tissues and angiogenic mediators which are able to improve damaged tissues. Mesenchymal stem cells are obtained from the human body by isolation, culture, proliferation, characterization, and/or differentiation originating from fat cells (adipose), periosteum tissue, and other tissues from the body. Mesenchymal stem cells can be obtained by autologous and allogenic way. Stem cell processing includes isolation, proliferation, differentiation, and temporary storage for clinical application adhering to good drug manufacturing practice. Approach to cell therapy and bioengineering in lung disease is rapidly developing in the last 10 years. In the current era of cell therapy and transplantation, a lot of research has been done to understand and develop mesenchymal stem cells as a therapeutic alternative, particularly in respiratory area.